2022
DOI: 10.3390/bios12100856
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide/Phosphorus-Doped Carbon Nitride Composite as Potential Scaffold for Electrochemical Detection of Nitrofurantoin

Abstract: Herein, we present an electrocatalyst constructed by zinc oxide hexagonal prisms/phosphorus-doped carbon nitride wrinkles (ZnO HPs/P-CN) prepared via a facile sonochemical method towards the detection of nitrofurantoin (NF). The ZnO HPs/P-CN-sensing platform showed amplified response and low-peak potential compared with other electrodes. The exceptional electrochemical performance could be credited to ideal architecture, rapid electron/charge transfer, good conductivity, and abundant active sites in the ZnO HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…This value indicated that the electrochemical reduction of NFT undergoes the equal number of protons and electrons. For further studies, PBS with pH 7.4 was chosen as the suitable electrolyte for the analysis of NFT in biological samples [46].…”
Section: Effect Of Ph On Nft Reductionmentioning
confidence: 99%
“…This value indicated that the electrochemical reduction of NFT undergoes the equal number of protons and electrons. For further studies, PBS with pH 7.4 was chosen as the suitable electrolyte for the analysis of NFT in biological samples [46].…”
Section: Effect Of Ph On Nft Reductionmentioning
confidence: 99%
“…While developing a new voltammetric approach, trials were carried out to integrate the working electrodes with various metallic nanostructures aiming at the enhancement of the sensor performance, which in turn improves the sensitivity and selectivity of the method. Based on their electrocatalytic activity and ability to catalyze the electrode process via a noticeable lowering of overpotential, metal oxide nanostructures act as one of the most common electrode modifiers. To the best that we can tell, no electroanalytical approach was reported for assaying of TIR, and the electrochemical analysis of TIR at carbon paste electrodes integrated with the copper oxide nanoparticles (CuONPs/CPE) is presented for the first time. It comprises investigations of the influence of the electrode modifier, pH of the supporting electrolyte, and variation of scan rate, and other measuring parameters were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics came into worldwide prominence since the advent of penicillin in 1941 and then revolutionizes the treatment of bacterial infections in animals and humans. , Animal meat is extensively accessible throughout all countries and is well accepted by consumers . The administration of antibiotic doses to livestock began experimentally in 1949 and practically in 1950 .…”
Section: Introductionmentioning
confidence: 99%